1998
DOI: 10.1046/j.1365-3180.1998.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal control of Chromolaena odorata in oil palm

Abstract: A range of herbicides was evaluated for the control of Chromolaena odorata (L.) K & R in oil palm at the Nigerian Institute for Oil Palm Research. Glufosinate‐ammonium quickly dessicated treated foliage but weed plants soon recovered. Glyphosate‐isopropylamine and glyphosate‐trimesium produced similar results, both formulations controlling treated vegetation and suppressing regrowth for up to 12 weeks after treatment. Triclopyr and hexazinone + diuron were effective for up to 20 WAT, whereas imazapyr controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Hemorrhage plant, Siam weed, giant sensitive plant, and giant potato are prominent weeds in cassava fields (Alabi et al 2001(Alabi et al , 2004aNzegbule and Ogunremi 1995;Tarawali et al 2013;Wakjira 2011). Siam weed and giant sensitive plant are reported as invasive species (Ikuenobe and Ayeni 1998;Uyi et al 2014) that reduce cassava root yield in the Humid Forest and Derived Savanna agroecologies in Nigeria. Alabi et al (2001) reported up to 85% root yield loss due to competition from giant sensitive plant and Nzegbule and Ogunremi (1995) reported significant cassava root yield reduction from competition with Siam weed.…”
Section: Resultsmentioning
confidence: 99%
“…Hemorrhage plant, Siam weed, giant sensitive plant, and giant potato are prominent weeds in cassava fields (Alabi et al 2001(Alabi et al , 2004aNzegbule and Ogunremi 1995;Tarawali et al 2013;Wakjira 2011). Siam weed and giant sensitive plant are reported as invasive species (Ikuenobe and Ayeni 1998;Uyi et al 2014) that reduce cassava root yield in the Humid Forest and Derived Savanna agroecologies in Nigeria. Alabi et al (2001) reported up to 85% root yield loss due to competition from giant sensitive plant and Nzegbule and Ogunremi (1995) reported significant cassava root yield reduction from competition with Siam weed.…”
Section: Resultsmentioning
confidence: 99%
“…Usually Chromolaena odorata RL K&R (Siam weed) constitutes an aggressive weed that is difficult to control in young single or mixed crop plantations of oil palm, rubber and cocoa in Nigeria. It also easily colonizes abandoned land in the rain forest and southern savannas of Nigeria and other parts of West Africa (Ivens, 1972; De Rouw, 1995; Ikuenobe & Ayeni, 1998) constituting an important member of the fallow vegetation. It is also a dominant fallow species in slash and burn agriculture of some parts of Asia including Thailand and India (Kushwaha et al ., 1981; Roder et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Para el cultivo de maíz, la aplicación es de 0.85 kg/ha y finalmente canola con 0.14 Kg/ha. Por otro lado, el cultivo de palma presentó los valores más altos con una aplicación del componente activo de glifosato de 2 kilos por hectárea según estudio realizado por Ikuenobe et al (1998). La deuda de carbono consiste en el balance de emisiones de dióxido de carbono debido a la conversión de ecosistemas nativos para la producción de biodiesel mediante la implantación de monocultivos.…”
Section: Aspectos Ambientalesunclassified